Canon 994: Granting Indulgences to an Orthodox Christian - Huels, John M. (Roman Replies and CLSA Advisory Opinions 2013, 2013)
In accord with canon 844 § 3, a priest visiting a hospital hears the confession of, anoints , and administers Viaticum to a dying Orthodox man. He also grants the Apostolic Pardon to the dying man after absolution. Now, he is wondering if he acted properly. May the Apostolic Pardon be given to non-Catholics in such a situation?